The idea of adaptation in transaction cost economics: an application to stakeholder theory - Vladislav Valentinov; Constantine Iliopoulos (Society and Business Review, 2024)
Purpose: Transaction cost economics sees a broad spectrum of governance structures spanned by two types of economic adaptation: autonomous and cooperative. Stakeholder theorists have drawn much inspiration from transaction cost economics but have not paid explicit attention to the centrality of the idea of adaptation in this literature. This study aims to address this gap. Design/methodology/approach: The authors develop a novel conceptual framework applying the distinction between the two types of economic adaptation to stakeholder theory. Findings: The authors argue that the idea of cooperative adaptation is particularly useful for describing the firm's collaboration with primary stakeholders in the joint value creation process. In contrast, autonomous adaptation is more relevant for firms interacting with secondary stakeholders who are not directly engaged in joint value creation and may not have formal contractual relationships with the firm. Accordingly, cooperative adaptation can be seen as vital for resolving team production problems affecting joint value creation, whereas autonomous adaptation addresses how the firm maintains legitimacy within the larger stakeholder environment. Originality/value: Similar to its significance for transaction cost economics, the distinction between the two types of adaptation equips stakeholder theory with a new systematic understanding of a potentially broad spectrum of firm–stakeholder collaboration forms.
Keywords: 330; autonomous adaptation; cooperative adaptation; stakeholder theory; transaction cost economics